Pulmonary arterial hypertension in adults with systemic right ventricles referred for cardiac transplantation. Issue 4 (5th March 2019) - Kim, Yuli Y.; Awh, Katherine; Acker, Michael; Atluri, Pavan; Bermudez, Christian; Crespo, Maria; Diamond, Joshua M.; Drajpuch, David; Forde‐Mclean, Rhondalyn; Fuller, Stephanie; Goldberg, Lee; Mazurek, Jeremy; et al.
Abstract: Background: Systemic right ventricular (RV) failure may progress necessitating referral for orthotropic heart transplantation (OHT). Pulmonary hypertension (PH) frequently coexists in adult congenital heart disease and can complicate the assessment for OHT. Methods: Single‐center case series of six patients (median age 34.9 years [IQR, 31.9‐42.4]) with systemic RV physiology with PH referred for OHT evaluation from 2008 to 2017. Results: One‐third (n = 6) of 18 patients with systemic RV physiology referred for OHT evaluation had pulmonary arterial hypertension (PAH) defined as mean pulmonary artery pressure (mPAP) > 25 mm Hg and pulmonary vascular resistance (PVR) > 3 Wood Units. Two of the six patients were considered OHT‐ineligible due to PH and comorbidities. Of the remaining four, two had pre‐capillary PH and underwent heart‐lung transplant (HLTx). The other two demonstrated reversibility of PVR with vasodilator testing and underwent OHT alone, one of whom died post‐transplant from PH crisis. Conclusions: Pulmonary arterial hypertension is common in systemic RV patients referred for OHT. Systemic RV dysfunction places these patients at risk for post‐capillary PH but pre‐capillary PH can exist. Despite management with selective pulmonary vasodilators and afterload reduction, criteria for listing patients for HLTx vs OHT are not known and need further elucidation.